Geoarchaeology as a tool to understand ancient navigation in the northern Persian Gulf and the harbour history of Siraf. (October 2020) - Pourkerman, Majid; Marriner, Nick; Morhange, Christophe; Djamali, Morteza; Spada, Giorgio; Amjadi, Sedighe; Vacchi, Matteo; Lahijani, Hamid; Esmaeili Jelodar, Mohammad; Tofighian, Hossein; Naderi Beni, Abdolmajid
Highlights: We present new geoarchaeological data from Siraf (Persian Gulf). Siraf dates back to the beginning of the current era. A second occupation phase began during the reign of Shapur II. Accessibility of this ancient harbour affected by various environmental factors. Abstract: Historical texts and archaeological studies attest to the maritime and trade importance of the Persian Gulf since the Sassanid Empires. Nonetheless, there is a paucity of data regarding ancient navigation and the reasons for a shift in maritime trade from the western (e.g. Shatt-al-Arab) to eastern (Siraf) Persian Gulf by the Abbasid dynasty. For some scholars, Siraf was occupied between 360 and 977 CE, after which time an earthquake entrained the demise of the city. However, it is unclear when Siraf was founded and how natural navigation conditions changed for ocean-going vessels in harbours of the NW Persian Gulf. To address this knowledge gap, we here present new geoarchaeological data from Siraf. Two anthropogenic facies were detected in drilled cores. They suggest that Siraf dates back to 2 BC-317 CE. After a hiatus, a second occupation phase began during the reign of Shapur II. Relative Sea-Level (RSL) fluctuations, climate change and Persian Gulf bathymetry all affected the possible nautical accessibility of this ancient Persian harbour. A fall in RSL, leading to a shortening of navigable water columns and amplified summer-time Shamal wind from 550 CE onwards possibly led to a loss in the importance of Shatt-al-Arab and other ports in the western Persian Gulf. It appears to have made Siraf the best alternative for seafarers. According to the wind regimes, the best time for arrival and departure from Siraf was August and October, respectively. RSL rise and increasing coastal erosion during the winter-time Shamal winds led to the degradation of harbour potentialities and was possibly at the origin of economic decline and poorly adapted harbour works at Siraf during a 150-year period between 850 and 1000 CE.